2004
DOI: 10.1177/1367493504041854
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis in Children and Young People: a Public Health Nurse Approach in New Zealand

Abstract: The involuntary passing of urine at age six and older is called enuresis. Wetting during the day is called diurnal enuresis and wetting at night while asleep is called nocturnal enuresis. Nocturnal enuresis is second only to allergy as the commonest chronic disorder in childhood. Many children (adolescents are included in the term 'children') who are nocturnal enuretics exhibit behaviours such as low self-esteem, withdrawal, less ambition and increased anxiety. These children are often low achievers within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Current practice parameters recommend the urine alarm as a first‐line treatment for NE (Kiddoo, ; Nevéus, ). This recommendation is consistent with other studies, suggesting that the urine alarm is more effective long term than medications such as desmopressin (DDAVP) and imipramine (see Friman, ; Heap, ; Klein, ). Medications have their place in a treatment plan, particularly if a child with NE does not respond positively to the urine alarm or an effective, short‐term option is required (Heap, ; Nevéus, ).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Current practice parameters recommend the urine alarm as a first‐line treatment for NE (Kiddoo, ; Nevéus, ). This recommendation is consistent with other studies, suggesting that the urine alarm is more effective long term than medications such as desmopressin (DDAVP) and imipramine (see Friman, ; Heap, ; Klein, ). Medications have their place in a treatment plan, particularly if a child with NE does not respond positively to the urine alarm or an effective, short‐term option is required (Heap, ; Nevéus, ).…”
supporting
confidence: 90%
“…The urine alarm literature identifies either a classical (i.e., alarm as unconditioned stimulus, bladder distention as unconditioned response, and waking as conditioned response) or operant (i.e., negative reinforcement or avoidance) conditioning paradigm as the mechanism of action, although some researchers recommend more studies to examine why the urine alarm works (Friman, ; Mellon & McGrath, ). Multiple reviews of the literature suggest that the urine alarm is effective for children with NE (Friman, ; Heap, ; Kiddoo, ; Mellon & McGrath, ). Specifically, Friman () noted that controlled studies indicate that the urine alarm's success rate (i.e., defined as complete cessation of wetting) is between 65% and 75% after 5–12 weeks of treatment with a 6‐month relapse rate of 15–30%, and Mellon and McGrath () found enough evidence for the urine alarm to be considered an effective treatment by the Chambless criteria standards (i.e., treatments demonstrating effectiveness through either at least two well‐designed group experiments or a large series of single case design experiments; Chambless et al., ).…”
mentioning
confidence: 99%
“…There have been some reports about the primary health care setting programs in the literature [16] . The authors concluded that nurses and nurse practitioners working in primary health care settings are in a position to manage the children experiencing nocturnal enuresis with such a program.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the high comorbidity of enuresis and various other psychiatric disorders is of particular import with respect to intervention. Given the reported association between enuresis and low self esteem (Butler 2004, Heap 2004), treatment of enuresis may reduce or alleviate disturbances of mood, which were found to be the highest comorbid diagnoses in this study. Furthermore, recent case reports have suggested that enuresis in children may be induced by resperidone (Herguner and Mukaddes 2007) and serotonin-selective re-uptake inhibitors , psychotropic medications commonly prescribed to ameliorate psychological disturbances.…”
Section: Discussionmentioning
confidence: 86%
“…Although research indicates a higher association of enuresis with externalising as opposed to internalising disorders, Desta et al (2007) reported children with anxiety disorders as being at greater risk for having enuresis. Furthermore, a number of investigations have suggested that reduced self esteem may be a consequence of enuresis, particularly among adolescents (Butler 2004, Heap 2004). More recently, Hyde et al (2008) suggested that childhood enuresis maybe a premorbid marker for neurodevelopmental abnormalities related to schizophrenia.…”
Section: Introductionmentioning
confidence: 98%